The Implementation of Oregon’s Death with Dignity Act: Reassuring, but More Data Are Needed - Orentlicher, David (2000)
Undoubtedly, empirical data from Oregon will play a key role for academics, legislators, judges, and the public as debate over the legalization of physician-assisted suicide continues. A central issue in the debate is whether a right to assisted suicide can be limited to only the truly compelling cases, or whether it will in practice be provided to patients who choose it out of depression, coercion, or misunderstanding. Empirical research can provide critical insights into this question